2020
DOI: 10.1002/jwmg.21854
|View full text |Cite
|
Sign up to set email alerts
|

Greater Sage‐Grouse Response to the Physical Footprint of Energy Development

Abstract: Energy infrastructure and associated habitat loss can lead to reduced reproductive rates for a variety of species including the greater sage‐grouse (Centrocercus urophasianus). Our goal was to refine our understanding of how the physical footprint of energy development relates to sage‐grouse nest and brood survival. Our survival analyses were conditional upon the amount of surface disturbance female sage‐grouse were exposed to during reproductive stages. We quantified levels of exposure and compared them to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
(105 reference statements)
2
7
0
Order By: Relevance
“…Additionally, there was weak evidence that the number of wind turbines within the late brood‐rearing home range negatively affected 42‐day brood success. These results support our predictions based on similar findings for sage‐grouse broods (LeBeau et al 2014, Kirol et al 2020) but are contrary to findings of Harrison (2015) and LeBeau et al (2017) who reported no effect of wind turbines on brood survival of prairie‐chickens and sage‐grouse, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, there was weak evidence that the number of wind turbines within the late brood‐rearing home range negatively affected 42‐day brood success. These results support our predictions based on similar findings for sage‐grouse broods (LeBeau et al 2014, Kirol et al 2020) but are contrary to findings of Harrison (2015) and LeBeau et al (2017) who reported no effect of wind turbines on brood survival of prairie‐chickens and sage‐grouse, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…A large majority of female use locations in the PPR had <3% disturbed surface within 1000 m, and mean and median values for disturbed and total anthropogenic surface around sage‐grouse used locations in all three seasons were also below or only slightly above BLM's 3% recommended surface disturbance cap, even in summer–fall, when females actively selected locations near pipelines and roads. These results are similar to those from six studies in Wyoming, where >90% of marked sage‐grouse locations occurred in areas with <3% disturbed surface (i.e., “press disturbance”; Kirol et al, 2020). Based on selection relationships during breeding and winter, disturbance caps should be set between 1.1% and 2.5% disturbed surface (see Figure 3a,e) or 1.8% and 3.5% total anthropogenic surface (see Figure 3b,f), to prevent detectable levels of avoidance in the PPR.…”
Section: Discussionsupporting
confidence: 88%
“…Previous analyses found the strongest support for selection in relation to landcover at 100 and 400‐m radii in this population (Walker et al, 2016). However, I also tested landcover and infrastructure cover within 1000 m because it matches maximum observed daily movement distances and the distance at which birds realistically perceive and respond to changes in landcover caused by energy infrastructure when selecting habitat within seasonal use areas is likely greater than 400 m (Dinkins et al, 2014; Kirol et al, 2020). Some infrastructure cover variables were standardized to a z ‐scale to facilitate model convergence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, existing research has focused on turbine proximity as an index of the expected magnitude of impact, yet proximity is at best an incomplete measure (LeBeau et al 2020 b ). Overall extent of surface disturbance may be more important (Kirol et al 2020). For example, the deleterious effects of oil and gas development tend to increase with well density (Doherty et al 2008, Green et al 2017) and in some cases are only detectable after a certain threshold of well density is passed (Doherty et al 2010, Harju et al 2010).…”
Section: Effects Of Wind Energy On Prairie Grousementioning
confidence: 99%